Dielectric Phase Transition Behaviour Study of Dry Route Derived (BA0.5 SN0.5) TIO3 Ceramics - Bhandari, Bhojraj; Pokheral, Bhadra Prasad (Journal of Nepal Chemical Society, 2019)
Ceramic materials display a wide range of properties that facilitate their use in many different product areas. Currently, there has been keen interest in the field of ceramic materials due to their excellent mechanical and physical properties. Barium Stannate Titanate (BST) is a binary solid solution system composed of ferroelectric Barium titanate and non-ferroelectric barium titanate. In this study, the phase transition behavior of (Ba1-xSnx)TiO3 (x = 0.5) (BST) ceramics was obtained by the dry-route method. The previous studies were based on Sn 2+ on the Ti site with varying values of x. The powders after calcination are compacted in the form of pellets using a hydraulic press at an optimized load above 70KN. The experimental density of our sample measured by liquid displacement method with glycerin was lower than theoretical density, giving the shape is highly dense with low porosity. The structure shows that on increasing the Sn2+ content volume decreases due to the size of Sn2+, which is smaller than that of Ba2+, in comparison to BaTiO3. As the demand of lead-free environment-friendly sensor is increasing, thus obtained BST has great applications as a sensor material in modern electronic devices.